2021
DOI: 10.1186/s40168-021-01083-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 detection status associates with bacterial community composition in patients and the hospital environment

Abstract: Background SARS-CoV-2 is an RNA virus responsible for the coronavirus disease 2019 (COVID-19) pandemic. Viruses exist in complex microbial environments, and recent studies have revealed both synergistic and antagonistic effects of specific bacterial taxa on viral prevalence and infectivity. We set out to test whether specific bacterial communities predict SARS-CoV-2 occurrence in a hospital setting. Methods We collected 972 samples from hospitalize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 71 publications
4
34
0
Order By: Relevance
“…Additionally, we found Rothia dentocariosa very abundant in deceased patients. This bacteria has been found as a causative agent of secondary pneumonia in H1N1 infection 33 and more recently has been associated with disease progression in previous studies characterizing the respiratory microbiota of COVID-19, proposing it as a biomarker for the disease 26 , 42 .…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, we found Rothia dentocariosa very abundant in deceased patients. This bacteria has been found as a causative agent of secondary pneumonia in H1N1 infection 33 and more recently has been associated with disease progression in previous studies characterizing the respiratory microbiota of COVID-19, proposing it as a biomarker for the disease 26 , 42 .…”
Section: Discussionmentioning
confidence: 95%
“…In [13] this genus was described as a major taxon in one of the throat microbial community types represented in patients but not in healthy controls. In another study, ASV identical to 16S rRNA of Rothia dentocariosa was found to be overrepresented in samples from COVID-19 patients [41]. There is also at least one published work describing the lower abundance of Rothia species in COVID-19 patients [42].…”
Section: Microbial Associations Of Disease Severity With Respect To Community Type Season and Comorbiditiesmentioning
confidence: 93%
“…Viral signatures have been demonstrated to persist up to 4 weeks in bulk floor dust collected from a room with a quarantined individual ( 6 ). Previous environmental monitoring studies have detected SARS-CoV-2 on surfaces contaminated by infected individuals in hospitals and congregate care facilities ( 6 10 ). Thus, indoor surface sampling can be valuable for detection of infected persons indoors, where transmission risk is highest ( 11 ).…”
Section: Observationmentioning
confidence: 99%